Pengantar Tentang Konsep Dasar Siaran Radio, Televisi, dan Multimedia (Internet) Bermuatan Dakwah - Erwan Efendi; Baharuddin Pasaribu; Hotna Marito Siregar (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Indonesia's creative da'wah media is developing along with advances in technology that have developed into an important component of modern society. Communicators can build da'wah on this foundation by presenting media in attractive packaging to facilitate distribution to the wider community. Da'i used to preach from the pulpit of mosques and other traditional places before spreading to television and radio. However, now there are many variants. Preachers currently use various means, one of which is social media, which is considered the easiest way to reach people. Nowadays, when it comes to social media, there are lots of influencers from artists, celebrities, or even young people who have creative ideas. These influencers give interesting presentations specifically discussing religious issues, either through Vlogs, Podcasts or Talkshows, which we usually do. Since the da'i's job is to encourage people to act in a good way according to God's commands, they are also known as influencers. The goal is to engage people but not force them, so you need to be creative and interesting. People won't immediately change their beliefs if you just show them kindness; instead, you will be educating them about the beauty of Islam. Therefore, preachers must be creative content creators (editors, layouters, designers). Preachers and media professionals can collaborate. Da'i can collaborate with celebrities and community leaders. Da'i can also collaborate with those in power. Keywords: Manages Programs, Media, Da'wah,